Benefit of Endovascular Thrombectomy by Mode of Onset: Secondary Analysis of the DAWN Trial. Issue 11 (November 2019) - Jadhav, Ashutosh P.; Aghaebrahim, Amin; Jankowitz, Brian T.; Haussen, Diogo C.; Budzik, Ronald F.; Bonafe, Alain; Bhuva, Parita; Yavagal, Dileep R.; Hanel, Ricardo A.; Hassan, Ameer E.; Ribo, Marc; Cognard, Christophe; et al.
Abstract : Background and Purpose—: It is unknown whether the benefit of thrombectomy in late presenting acute stroke patients with imaging evidence of clinical-infarct mismatch is different in patients presenting with wake-up stroke compared with those presenting with witnessed onset or unwitnessed onset. Methods—: Prespecified secondary analysis was performed from DAWN (Diffusion Weighted Imaging [DWI] or Computerized Tomography Perfusion [CTP] Assessment With Clinical Mismatch in the Triage of Wake Up and Late Presenting Strokes Undergoing Neurointervention), a multicenter, prospective, randomized clinical trial with blinded end point assessment comparing thrombectomy with the Trevo device against standard medical therapy in patients with acute stroke and clinical-infarct mismatch presenting 6 to 24 hour after the time last seen well. For the purposes of this study, the primary outcome was the proportion of modified Rankin Scale score 0 to 2 at 90 days. Univariable analysis and multivariable logistic regression was used to assess the relationship between outcome and mode of onset. Results—: All 206 enrolled patients were included in the study. Mode of onset was: wake-up stroke (55.3%, n=114), witnessed onset (12.1%, n=25), and unwitnessed onset (32.5%, n=67) with median time last seen well to randomization (13.4±3.7, 10.0±3.7, 14.1±4.9 hours) respectively. Rates of 90-day modified Rankin Scale score of 0 to 2 and symptomatic intracerebral hemorrhage in the thrombectomy arm were not statistically different across patient onset subtypes ( P =0.79 and P =0.40, respectively). The benefit of thrombectomy compared with best medical therapy was maintained across all 3 onset modes (rates of 90-day modified Rankin Scale score of 0 to 2 in patients allocated to thrombectomy versus control: wake-up stroke—49.3% versus 10.6%, witnessed onset—63.6% versus 21.4%, UW—41.4% versus 13.2%; P ×interaction=0.79). In univariable and multivariable analyses, mode of onset was not identified as a significant predictor of modified Rankin Scale score 0 to 2 at 90 days. Conclusions—: In patients with acute ischemic stroke presenting between 6 and 24 hours from time last seen well and harboring clinical-infarct mismatch, the benefit of thrombectomy was similar regardless of the wake-up, unwitnessed, or witnessed mode of onset.